2014
DOI: 10.1021/cm502689x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Properties of Amorphous Indium Oxide

Abstract: A series of In2O3 thin films, ranging from X-ray diffraction amorphous to highly crystalline, were grown on amorphous silica substrates using pulsed laser deposition by varying the film growth temperature. The amorphous-to-crystalline transition and the structure of amorphous In2O3 were investigated by grazing angle X-ray diffraction (GIXRD), Hall transport measurement, high resolution transmission electron microscopy (HRTEM), electron diffraction, extended X-ray absorption fine structure (EXAFS), and ab initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
183
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(197 citation statements)
references
References 44 publications
14
183
0
Order By: Relevance
“…Structural parameters of Bi‐0%, Bi‐0.5%, and Bi 2 O 3 reference samples were quantitatively determined through fitting of EXAFS spectra (Figure S6, Supporting Information) as summarized in Table S1 (Supporting Information). In theory, In 2 O 3 has the bixbyite crystal structure, with all indium cations surrounded by six oxygen atoms (CN In—O = 6) and two distinct sets of adjacent polyhedral In—In neighbors (CN In−In = 6, at a distance of ≈3.34 Å, and CN In—In* = 6, at a distance of ≈3.83 Å) 27. In the present study, the prepared Bi‐0% sample has longer In—In distances (3.36 and 3.84 Å) and lower coordination numbers (5.1 and 3.1), suggesting structural distortion caused by defects, which is consistent with the observed presence of surface hydroxide and oxygen vacancy 28.…”
Section: Resultsmentioning
confidence: 99%
“…Structural parameters of Bi‐0%, Bi‐0.5%, and Bi 2 O 3 reference samples were quantitatively determined through fitting of EXAFS spectra (Figure S6, Supporting Information) as summarized in Table S1 (Supporting Information). In theory, In 2 O 3 has the bixbyite crystal structure, with all indium cations surrounded by six oxygen atoms (CN In—O = 6) and two distinct sets of adjacent polyhedral In—In neighbors (CN In−In = 6, at a distance of ≈3.34 Å, and CN In—In* = 6, at a distance of ≈3.83 Å) 27. In the present study, the prepared Bi‐0% sample has longer In—In distances (3.36 and 3.84 Å) and lower coordination numbers (5.1 and 3.1), suggesting structural distortion caused by defects, which is consistent with the observed presence of surface hydroxide and oxygen vacancy 28.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, instead of classical atomistic approaches commonly employed for modeling of glasses, quantum-mechanical molecular dynamics simulations combined with accurate densityfunctional calculations are required for AOSs in order to reliably describe the formation of both shallow and deep defects responsible for carrier generation and the charge transport limited by electron scattering and trapping. In addition, accurate characterization of the structural features beyond the first shell (i.e., beyond the nearest neighbors) is necessary in order to explain the high sensitivity of the AOSs properties to the deposition [84] and post-deposition conditions, [64] particularly oxygen environment, [85] as well as the chemical composition of the sample. [67,86] In this work, ab initio MD simulations and hybrid-functional DFT-based electronic structure calculations are performed i) to systematically study the local and medium-range structural characteristics of several prototype In-based oxides with different degree of amorphization, oxygen stoichiometry, cation composition, and/or lattice strain and ii) to connect the structural peculiarities to the resulting electronic, optical, or thermal properties of each material.…”
Section: Mechanical Brittle Bendablementioning
confidence: 99%
“…Consequently, the two peaks in the In-In distribution are nearly indistinguishable and hard to resolve experimentally (i.e., the coordination number and Debye-Waller factor for the second and third shells cannot be uniquely fit). Yet, information regarding the In-In shells is essential for understanding the properties of AOSs: it has been shown that medium-range ordering plays a crucial role in the carrier transport of amorphous indium oxide [84] as discussed in the next section.…”
Section: Key Structural Properties Of Amorphous Indium Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…Some important findings related to the internal structure of metallic glass, e.g., short-range order [2,3], medium-range order [4,5], polymorphism [6], and long-range topological order [7], have been reported recently. Effort has also been devoted to the study of local atomic environment [8,9] and lithium transport [10] in other kinds of amorphous materials. Furthermore, their specific atomic arrangement enables amorphous materials to exhibit high performance in mechanics and catalysis [11][12][13][14], as well as interesting magnetic properties [15][16][17].…”
Section: Introductionmentioning
confidence: 99%